Health-related quality of life among adults living with chronic non-communicable diseases in the Ho Municipality of Ghana: a health facility-based cross-sectional study - William Kwame Witts; Hubert Amu; Robert Kokou Dowou; Frank Oppong Kwafo; Luchuo Engelbert Bain (BMC, 2024)
Abstract Background Morbidity and mortality rates from chronic non-communicable diseases (CNCDs) are increasing globally. In Ghana, CNCDs account for 43% of all deaths. We examined the Health-Related Quality of Life (HRQoL) and associated factors among adults living with CNCDs in the Ho Municipality. Methods This was a health facility-based descriptive cross-sectional study among 432 adults living with cancer, diabetes, chronic kidney disease (CKD), stroke, and hypertension in the Ho Municipality of Ghana. The study adopted the EQ-5D-5L instrument and the Ugandan value set to compute respondents' HRQoL index. Quantile regression models were used in analysing the data with STATA v17.0 at 95% Confidence Intervals, and statistical significance set at p < 0.05. Results 63.7% of our respondents reported having a problem across the five dimensions of the EQ-5D-5L. The most problems were reported in the dimensions "Anxiety/Depression" (94.4%) and "Pain/Discomfort" (91.4%). Divorced/separated respondents (aOR=-0.52, 95% CI=-0.71, -0.33) and those living with comorbidities (aOR=-0.95, 95% CI=-0.15, -0.04,) were less likely to report high index for HRQoL. However, respondents diagnosed with CKD (aOR = 0.26, 95% CI = 0.10, 0.42), diabetes (aOR = 0.28, 95% CI = 0.11, 0.45), hypertension (aOR = 0.35, 95% CI = 0.19, 0.50) and stroke (aOR = 0.26, 95% CI = 0.11, 0.40) were more likely to report higher index than those diagnosed with cancer. Conclusion Our study revealed elevated proportions of reported problems in the "Anxiety/Depression" and "Pain/Discomfort" dimensions, indicating noteworthy concerns in these areas of HRQoL. The prevalent issues reported across HRQoL dimensions are cause for concern, posing potential exacerbation of health conditions. We advocate for collaborative efforts from the Ministry of Health, Ghana Health Service, and relevant stakeholders to scrutinize and implement interventions targeting social and psychological factors. These efforts should specifically address contributors to diminished health-related quality of life, particularly among less educated, divorced, and comorbid individuals.